WHO recommendations for misoprostol use for obstetric and gynecologic indications. Issue 2 (19th February 2013) - Tang, Jennifer; Kapp, Nathalie; Dragoman, Monica; de Souza, Joao Paulo
Abstract: Background: Misoprostol, a prostaglandin E1 analog, stimulates uterine contractility and cervical ripening. A number of randomized trials and systematic reviews have evaluated its use in obstetric and gynecologic conditions. Misoprostol is inexpensive, stable at room temperature, and available in more than 80 countries, making it particularly useful in resource‐poor settings. WHO recognizes the crucial role of misoprostol in reproductive health and has incorporated recommendations for its use into 4 reproductive health guidelines focused on induction of labor, prevention and treatment of postpartum hemorrhage, and management of spontaneous and induced abortion. Methods and results: All guidelines were prepared in accordance with the WHO Handbook for Guideline Development . The process included: identification of priority questions and critical outcomes; retrieval of evidence; assessment and synthesis of evidence; formulation of recommendations; and planning for dissemination, implementation, impact evaluation, and updating. The present report summarizes recommendations for misoprostol use in line with each guideline. Conclusion: The present comprehensive reference document was designed to enable clinicians and policy makers to quickly access and compare recommendations for the use of misoprostol in various reproductive health settings.